The hoverflies: a case of "poor" mimicry? - Grewcock, David A. (1992)
The hoverflies (Diptera:Syrphidae) represent an apparently paradoxical visual Batesian mimicry complex, with what appear to be "poor" Mimics outnumbering their more accomplished counterparts. The purpose of this thesis is to determine how far conventional mimicry theory is capable of explaining the apparent paradoxes of mimicry in the hoverflies.